ASSOCIATION BETWEEN EARLY LIFE GROWTH AND BLOOD PRESSURE TRAJECTORIES IN BLACK SOUTH AFRICAN CHILDREN - Kagura, Juliana (Hypertension, 2016)
Early growth is associated with blood pressure measured on one occasion, but whether early life growth patterns are associated with longitudinal blood pressure trajectories is under-researched. Therefore, we sought to examine the association between early growth and blood pressure trajectories from childhood to adulthood. Blood pressure was measured on seven occasions between ages 5 and 18 years in the Birth to Twenty cohort study and conditional variables for growth in infancy and mid-childhood were computed from anthropometric measures (n=1937, 52% girls). We used a group-based trajectory modeling approach to identify distinct height-adjusted blood pressure trajectories and then tested their association with growth between birth and mid-childhood adjusting for several covariates. Three trajectory groups were identified for systolic and diastolic blood pressure: ‘lower’, ‘middle’ and ‘upper’ in boys and girls, separately. In boys, predictors of the middle or upper systolic blood pressure trajectories versus the lower trajectory were in birth weight (odds ratio [OR] 0.75[95% CI 0.58–0.96] per SD) and relative weight gain in infancy (4.11[1.25–13.51] per SD). In girls, greater relative weight gain and linear growth in both infancy and mid-childhood were consistently associated with an almost 2-fold higher likelihood of being in the upper versus lower systolic blood pressure trajectory. The associations for the diastolic blood pressure trajectories were inconsistent. These findings emphasize the importance of identifying children at risk of progression to high blood pressure. Accelerated growth in infancy and mid-childhood may be a key target for early life intervention in prevention of elevated blood pressure progression.